(untitled) (Tempo e Argumento, 2012)
This article examines the work of Darcy Ribeiro, principally the book O Povo Brasileiro (1995). It is focusing about the relationship between miscegenation and identity according to the thought of the author. We try to understand how the Brazil is identified as a new people, a singular ethnic identity arising from the mixture of different peoples with different racial, cultural, linguistics characteristics. Thus, the intense mixing, biological and cultural, is the fundamental element to understand the formation of the Brazilian people, moreover, these are determinant to the formation of the specific ethnic identity of the Brazilian people.